A rare case of gastrointestinal stromal tumors presenting with jejuno-jejunal intussusception and anemia in elderly - Haridas, Abhilash; Mukker, Payal; Hameed, Shine (International Journal of Research in Medical Sciences, 2017)
Jejuno-jejunal intussusception is a rare occurrence in the context of a gastrointestinal stromal tumor (GIST). We present the case of an elderly female with recurrent episodes of small bowel obstruction and anemia due to blood loss caused by jejunal GIST with jejuno-jejunal intussusception.